Manajemen Media Massa Hizbut Tahrir Indonesia - Sabari Sabari (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2017)
The background of this research is based on the access of people in Sambas Regency, West Kalimantan Province who know and read the bulletin of Al-Islam published by Hizbut Tahrir Indonesia (HTI). It’s happen because the Bulletin Al-Islam is widely circulated in mosques in Sambas District. The purpose of this research is to know the publishing management of bulletin Al-Islam issued by HTI of Sambas Regency. This research uses qualitative method with field research and using case study. The results of this study are firstly the topic of news prioritized by editors of Al-Islam bulletin is the news that is discussed by reader of Sambas Regency. Secondly, the editorial frames of language and facts are in line with the perceived by the readers, as a result it is personal interaction between the bulletin and the readers. Thirdly, the editor frames the bulletin for gaining intention and response of the event so the local governments could make policies that can realize the concept of Khilafah Al-Islamiyah through the local regulations. Latar belakang penelitian ini didasarkan pada banyaknya masyarakat Kabupaten Sambas Provinsi Kalimantan Barat yang mengetahui dan membaca buletin Al-Islam yang diterbitkan oleh Hizbut Tahrir Indonesia (HTI). Ini terjadi karena Buletin Al-Islam banyak beredar di masjid-masjid di Kabupaten Sambas. Untuk itu penelitian ini ingin mengetahui bagaimana manajemen penerbitan buletin Al-Islam yang diterbitkan HTI Kabupaten Sambas. Penelitian ini menggunakan metode kualitatif dengan jenis penelitian field research dan menggunakan pendekatan studi kasus. Adapun hasil dari penelitian ini di antaranya pertama, topik berita yang diprioritaskan redaksi buletin Al-Islam adalah berita yang sedang hangat dibahas masyarakat Kabupaten Sambas. Kedua, redaksi membingkai bahasa dan fakta yang sesuai dengan yang dirasakan masyarakat sehingga terjadi interaksi personal antara buletin dan pembaca. Ketiga, redaksi membingkai buletin dengan maksud memberikan sebuah tanggapan dalam peristiwa yang terjadi agar pemerintah daerah membuat kebijakan yang dapat mewujudkan konsep khilafah Al-Islamiyah melalui peraturan-peraturan daerah.